2013
DOI: 10.1113/jphysiol.2012.247973
|View full text |Cite
|
Sign up to set email alerts
|

Endoperoxide 4 receptors play a role in evoking the exercise pressor reflex in rats with simulated peripheral artery disease

Abstract: Key points• In decerebrated rats, the exercise pressor reflex arising from a hindlimb whose femoral artery was occluded for 72 h was significantly higher than that arising from a hindlimb whose femoral artery was freely perfused.• Blockade of endoperoxide 4 receptors, but not blockade of endoperoxide 3 receptors, prevented the exaggerated exercise pressor reflex in rats with ligated femoral arteries.• Blockade of endoperoxide 3 or 4 receptors in rats with freely perfused femoral arteries had no effect on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 39 publications
5
40
2
Order By: Relevance
“…In particular, 72 h of femoral artery ligation elicited a higher BP response to static contraction compared with control conditions (i.e., freely perfused femoral artery), and this augmented pressor response was attenuated by daltroban, a thromboxane receptor antagonist (18). In another study, Yamauchi and colleagues (41) showed that 72 h of femoral artery ligation increased endoperoxidade 4 receptor (a receptor for PGE 2 ) protein in the dorsal root ganglia; blockade of these receptors lowered the exercise pressor reflex. More recently, it has been shown that ketorolac administered into the spinal cord attenuated the pressor response to static contraction in rats (37).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, 72 h of femoral artery ligation elicited a higher BP response to static contraction compared with control conditions (i.e., freely perfused femoral artery), and this augmented pressor response was attenuated by daltroban, a thromboxane receptor antagonist (18). In another study, Yamauchi and colleagues (41) showed that 72 h of femoral artery ligation increased endoperoxidade 4 receptor (a receptor for PGE 2 ) protein in the dorsal root ganglia; blockade of these receptors lowered the exercise pressor reflex. More recently, it has been shown that ketorolac administered into the spinal cord attenuated the pressor response to static contraction in rats (37).…”
Section: Discussionmentioning
confidence: 96%
“…The findings in the present study that, following exercise training, the muscle mechanoreflex-mediated increase in MSNA is significantly diminished, and this decrease is accompanied by a significant decrease in COX-2 expression in the VL muscle, support the notion that overexpression of COX-2 in the skeletal muscle of HF patients leads to increased prostaglandin (likely PGE 2 ) sensitization of group III afferents. The expression of the EP 4 receptor, which is present on DRG and is responsible for afferent nerve sensitization by PGE 2 (52), is also decreased following exercise training. Similarly, the expression of the TP receptor, which is responsible for the afferent sensitization by TXA 2 is decreased following exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Yamauchi et al (2013) found that blocking EP4 receptors by injecting L, 161-982 into the femoral artery of a ligated rat, but not that of a freely perfused rat, attenuated the pressor response to static contraction. EP3 receptor blockade did not attenuate the response.…”
Section: Mechanisms Contributing To Exaggerated Pressor Responsementioning
confidence: 92%